Pengetahuan Perawat Tentang Komunikasi Terapeutik Di Rumah Sakit - Darmi Arda (Jurnal Ilmiah Kesehatan Sandi Husada, 2019)
Communication is an important part of human life. Throughout the course of his life humans always communicate whether consciously or not. The ability of nurses in conducting therapeutic communication is an important thing in the implementation of nursing care. The nurse must not look confused, the patient must feel that he is the nurse's main focus during the interaction. So that nurses can play an active and therapeutic role, nurses must analyze themselves including self-awareness, clarification of values, feelings and being able to be a responsible model. The purpose of this study is descriptive research in which the measurement results are presented as is. This research method uses descriptive research. Descriptive research is research in which the researcher only does a description of the phenomenon found, where the measurement results are presented as is without analyzing why the phenomenon occurred. By using this type of research, researchers wanted to obtain information about the demographic data of nurses and the level of nurse knowledge about therapeutic communication. The results of this study showed that in general the level of hospital nurses' knowledge about therapeutic communication was included in both categories. Of the 52 respondents studied, it was found that respondents with good knowledge were 45 people (86.5%) and respondents with less knowledge were 7 people (13.5%).The conclusion of this study was the knowledge of nurses working in Makassar hospitals about therapeutic communication in general is included in either category.